Plastoquinone and Ubiquinone in Plants: Biosynthesis, Physiological Function and Metabolic Engineering - Liu, Miaomiao; Lu, Shanfa (Frontiers in Plant Science, 2016)
Plastoquinone (PQ) and ubiquinone (UQ) are two important prenylquinones, functioning as electron transporters in the electron transport chain of oxygenic photosynthesis and the aerobic respiratory chain, respectively, and play indispensable roles in plant growth and development through participating in the biosynthesis and metabolism of important chemical compounds, acting as antioxidants, being involved in plant response to stress, and regulating gene expression and cell signal transduction. UQ, particularly UQ10, has also been widely used in people’s life. It is effective in treating cardiovascular diseases, chronic gingivitis and periodontitis, and shows favorable impact on cancer treatment and human reproductive health. PQ and UQ are made up of an active benzoquinone ring attached to a polyisoprenoid side chain. Biosynthesis of PQ and UQ is very complicated with more than thirty five enzymes involved. Their synthetic pathways can be generally divided into two stages. The first stage leads to the biosynthesis of precursors of benzene quinone ring and prenyl side chain. The benzene quinone ring for UQ is synthesized from tyrosine or phenylalanine, whereas the ring for PQ is derived from tyrosine. The prenyl side chains of PQ and UQ are derived from glyceraldehyde 3-phosphate and pyruvate through the 2-C-methyl-D-erythritol 4-phosphate pathway and/or acetyl-CoA and acetoacetyl-CoA through the mevalonate pathway. The second stage includes the condensation of ring and side chain and subsequent modification. Homogentisate solanesyltransferase, 4-hydroxybenzoate polyprenyl diphosphate transferase and a series of benzene quinone ring modification enzymes are involved in this stage. PQ exists in plants, while UQ widely presents in plants, animals and microbes. Many enzymes and their encoding genes involved in PQ and UQ biosynthesis have been intensively studied recently. Metabolic engineering of UQ10 in plants, such as rice and tobacco, has also been tested. In this review, we summarize and discuss recent research progresses in the biosynthetic pathways of PQ and UQ and enzymes and their encoding genes involved in side chain elongation and in the second stage of PQ and UQ biosynthesis. Physiological functions of PQ and UQ played in plants as well as the practical application and metabolic engineering of PQ and UQ are also included.